Cover Feature: Four‐Component One‐Pot Process Involving Passerini Reaction Followed by Aldol Addition and Transesterification (Eur. J. Org. Chem. 23/2020). Issue 23 (17th June 2020) - Hasan, Muhammad; Zaman, Manzoor; Peshkov, Anatoly A.; Amire, Niyaz; Les, Adil; Nechaev, Anton A.; Wang, Yuqing; Kashtanov, Stepan; Van der Eycken, Erik V.; Pereshivko, Olga P.; Peshkov, Vsevolod A.
Abstract : The Cover Feature shows a novel four‐component one‐pot transformation that makes use of carboxylic acids, isocyanides, aryl glyoxals, and ethyl glyoxalate to assemble densely functionalized tartaric acid derivatives. The chemical diversity of the studied process is linked to a variety of the author's affiliations and countries of origin through the silk road‐related artwork. Amir Khuzhaev (ALECTIUS) is gratefully acknowledged for the help with graphic design. Graphic elements are designed by freepik.com . More information can be found in the Full Paper by A. A. Peshkov, V. A. Peshkov et al.